DAMPAK PENGGUNAAN METODE BELAJAR SAMBIL BELAJAR PADA PEMBELAJARAN IPS “ Daerahku Kebanggaanku” DI KELAS V SDN 02 TAEH BUKIK KECEMATAN PAYAKUMBUH - Velina Safitri; Ulfa Nabila; viona ramadhani; Zonatul Fajira; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine the effect of the application of Game-Based Learning methods in improving the social skills of fifth-grade elementary school students, especially in learning Social Studies about "My Proud Region". This study used a qualitative approach, with data collection through interviews with class teachers and observations of the learning process at SDN 02 Taeh Bukik, Payakumbuh District. Research findings indicate that game-based learning positively impacts student engagement, increases communication skills, strengthens group collaboration, and boosts self-confidence. Game-based activities, such as travel puzzles that require students to match regional potential cards to maps, successfully create a fun, active, and interactive learning environment. Furthermore, this method helps students better understand the material because they learn from direct experience. However, there are several challenges in implementing this method, such as a lack of effective time management, overcrowded classrooms, and the need for more time and effort from teachers to prepare game media. Therefore, game-based learning can be an innovative alternative in teaching social studies at the elementary school level if properly designed and managed.